COVID-19 living evidence synthesis #8 (version 2): What is the effectiveness of available COVID-19 vaccines in children and adolescents in general and specifically for variants of concern? - Flórez, ID; Velásquez-Salazar, P; Martínez, JC; Linkins, L; Abdelkader, W; Iorio, A; Lavis, JN; Patiño-Lugo, DF (My University, 2022)
An in-depth synthesis of what is known, based on the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies), about the effectiveness of available COVID-19 vaccines in children and adolescents in general and specifically for variants of concern.
Keywords: effectiveness; COVID-19; vaccines; children; adolescents; variants